2020
DOI: 10.1016/j.jcmg.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Right Ventricular Longitudinal Strain in Patients With COVID-19

Abstract: The aim of this study was to investigate whether right ventricular longitudinal strain (RVLS) was independently predictive of higher mortality in patients with coronavirus disease-2019 .BACKGROUND RVLS obtained from 2-dimensional speckle-tracking echocardiography has been recently demonstrated to be a more accurate and sensitive tool to estimate right ventricular (RV) function. The prognostic value of RVLS in patients with COVID-19 remains unknown.METHODS One hundred twenty consecutive patients with COVID-19 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
498
12
25

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(573 citation statements)
references
References 25 publications
38
498
12
25
Order By: Relevance
“…Our data also showed that elevated PASP on echocardiogram was an independent predictor of death. Our study corroborates with other literature which suggests that elevated PASP was related to morbidity (32). A case series also noted elevated PASP in their patients, which could be explained by pulmonary hypertension or recurrent pulmonary-embolic disease (37,40).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data also showed that elevated PASP on echocardiogram was an independent predictor of death. Our study corroborates with other literature which suggests that elevated PASP was related to morbidity (32). A case series also noted elevated PASP in their patients, which could be explained by pulmonary hypertension or recurrent pulmonary-embolic disease (37,40).…”
Section: Discussionsupporting
confidence: 92%
“…The commonest echocardiogram abnormality noted in our study was TR, similar to ndings from another study (31), and under one third of our patients demonstrated RV dysfunction. The latter could be secondary to the acute respiratory distress syndrome seen in critically ill COVID-19 patients, which results in RV systolic dysfunction (8,32,33). Despite not being overly sensitive for a pulmonary embolism (PE), echocardiographic features of right heart strain and right heart dysfunction can indicate the presence of a pulmonary embolus (PE) or Pulmonary Intravascular Coagulation (PIC) which has been hypothesised to be one of the causative mechanisms leading to respiratory distress in COVID-19 patients (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study also demonstrated that compared with survivors, nonsurvivors displayed enlarged right heart chambers, diminished RV function, and elevated pulmonary artery systolic pressure. 14…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive evaluation of these patients, including clinical, basic, and advanced ultrasonographic parameters, could be useful for an accurate prognostic assessment: In fact, it has been demonstrated that, in patients with acute HF, underlying pathologies, changes in renal function and TTE findings are associated with mortality 42 . Moreover, a recent study by Li et al investigating inhospital mortality in 120 patients with COVID‐19 has shown RV dilation and dysfunction in nonsurvivors and found global right ventricular longitudinal strain (RVLS) < 23% to be an independent predictor of mortality with multivariate analysis (AUC = 0.87, P < .001) 43 …”
Section: Acute Heart Failurementioning
confidence: 99%